Specific gamma‐aminobutyrate chemotaxis in pseudomonads with different lifestyle. Issue 3 (26th May 2015) - Reyes‐Darias, Jose Antonio; García, Vanina; Rico‐Jiménez, Miriam; Corral‐Lugo, Andrés; Lesouhaitier, Olivier; Juárez‐Hernández, Dalia; Yang, Yiling; Bi, Shuangyu; Feuilloley, Marc; Muñoz‐Rojas, Jesús; Sourjik, Victor; Krell, Tino
Summary The PctC chemoreceptor of Pseudomonas aeruginosa mediates chemotaxis with high specificity to gamma‐aminobutyric acid (GABA). This compound is present everywhere in nature and has multiple functions, including being a human neurotransmitter or plant signaling compound. Because P. aeruginosa is ubiquitously distributed in nature and able to infect and colonize different hosts, the physiological relevance of GABA taxis is unclear, but it has been suggested that bacterial attraction to neurotransmitters may enhance virulence. We report the identification of McpG as a specific GABA chemoreceptor in non‐pathogenic Pseudomonas putida KT2440. As with PctC, GABA was found to bind McpG tightly. The analysis of chimeras comprising the PctC and McpG ligand‐binding domains fused to the Tar signaling domain showed very high GABA sensitivities. We also show that PctC inactivation does not alter virulence in Caenorhabditis elegans. Significant amounts of GABA were detected in tomato root exudates, and deletion of mcpG reduced root colonization that requires chemotaxis through agar. The C. elegans data and the detection of a GABA receptor in non‐pathogenic species indicate that GABA taxis may not be related to virulence in animal systems but may be of importance in the context of colonization and infection of plant roots by soil‐dwelling pseudomonads.